Presenilin Deficiency Increases Susceptibility to Oxidative Damage in Fibroblasts - Zou, Kun; Islam, Sadequl; Sun, Yang; Gao, Yuan; Nakamura, Tomohisa; Komano, Hiroto; Tomita, Taisuke; Michikawa, Makoto (Frontiers in Aging Neuroscience, 2022)
Alzheimer’s disease (AD) is a genetic and sporadic neurodegenerative disease characterized by extracellular amyloid-β-protein (Aβ) aggregates as amyloid plaques and neuronal loss in the brain parenchyma of patients. Familial AD (FAD) is found to be genetically linked to missense mutations either in presenilin (PS) or amyloid precursor protein (APP). Most of PS mutations increase Aβ42/Aβ40 ratio, which is thought to result in early amyloid deposition in brain. However, PS deficiency in the fore brain of adult mouse leads to neuronal loss in an Aβ independent manner and the underlying mechanism is largely unknown. In this study, we found that reactive oxygen species (ROS) are increased in PS deficient fibroblasts and that H2O2 and ferrous sulfate treatment produced more ROS in PS deficient fibroblasts than in wild-type fibroblasts. PS deficient fibroblasts showed significantly decreased cellular ferritin levels compared with wild-type fibroblasts, suggesting reduced iron sequestrating capability in PS deficient cells. Blockade of γ-secretase activity by a γ-secretase inhibitor, DAPT, decreased ferritin levels, indicating that γ-secretase activity is important for maintaining its levels. Moreover, overexpression PS1 mutants in wild-type fibroblasts decreased ferritin light chain levels and enhanced intracellular ROS levels. Our results suggest that dysfunction of PS may reduce intracellular ferritin levels and is involved in AD pathogenesis through increasing susceptibility to oxidative damage.